Autologous and allogenic systems of HIV expansion: what is the better choice for clinical application in therapeutic vaccine?. (December 2013) - Silva, Lais Teodoro da; Pontillo, Alessandra; da Silva, Wanessa Cardoso; Almeida, Alexandre de; Duarte, Alberto José da Silva; Oshiro, Telma Miyuki
Aims: HIV-1 expanded in an allogenic system (Al-HIV) represents a cheaper and faster alternative to the autologous virus (Au-HIV) as an antigen in anti-HIV immunotherapy. In this study, chemically inactivated HIV-1 obtained through autologous or allogenic systems were compared.Patients & methods: Au-HIV and Al-HIV obtained from cultures of peripheral blood mononuclear cells from 11 HIV + individuals were tested for virus production, yield and time of culture, and their ability to elicit a specific immune response in vitro .Results: The allogenic system was more efficient than the autologous system. Dendritic cells pulsed with Au-HIV and Al-HIV presented a similar phenotypic profile, but only Al-HIV induced a significant increase in IFN-γ + lymphocytes.Conclusion: The use of an allogenic system displays several advantages in terms of cell manipulation, time and cost of culture, and immunogenicity.